BOARD CHARACTERISTICS AND CORPORATE SOCIAL RESPONSIBILITY PRACTICES: IN UPPER ECHELON THEORY PERSPECTIVE EVIDENCE FROM SRI LANKAN FIRMS - Thambugala, T.; Rathwatta, H. (University of Jaffna, 2021)
Due to the heightened competition and advancements in the dynamic business environment, considerable attention is given to Corporate Social Responsibility (CSR). Most studies on CSR are quantitative and focused on linear relationships with profitability, firm characteristics, corporate governance and board diversity. However, little is known on how boardcharacteristics influence CSR Practices. Therefore, this qualitative study focuses on how board characteristics affect CSR practices in Sri Lankan contextfrom Upper Echelon theory (UET) perspective. The data was gathered via in-depth interviews conducted with directors in selected companies in Sri Lanka. The study revealed that both male and female directors have equal opportunity to raise voice on CSR in board discussions and female directors are more interested in CSR practices relating to women and children due to their psychological cognitive such asinherent compassion, empathy and understanding of women’s needs. The directors with multiple educational and professional qualifications, especially in accountancy, showed a sound knowledge on CSR. Further, well-experienced directors in multiple industries are also more concernedwith CSR and suggested genuine CSR practice as most companies use CSR as a promotional tool for building corporate image. It was further evident that the foreign directors have more exposure on CSR. According to the UET perspective, the different characteristics of upper echelon (board of directors) influence CSR practices.
Keywords: Corporate social responsibility; Board characteristics; Upper echelon theory